1972
DOI: 10.4098/at.arch.72-30
|View full text |Cite
|
Sign up to set email alerts
|

Macromorphological description of the genital organs of the female beaver

Abstract: A description is given of organa genitalia feminina of the beaver, Castor fiber L. It was found that cervix uteri has two canales cervicis and the other paired parts of the uterus are not differentiated into corpus and cornua. The long vagina runs to the rear into a strongly developed vestibulum vaginae, opening together with the rectum into pseudocloaca. Vestibulum vaginae has the large diverticula lateralia vestibuli vaginae characteristic of this species, termed praeputial »glands«, in which castoreum is se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…In the same way as in females, both the sacs producing castoreum, of similar dimensions and size, and the circumanal glands, are situated in this region. The first of these in females open into the region of the clithoris and are the lateral diverticuli of this region (Gienc & Doboszyńska, 1972), whereas in males they open near the penis and are quite clearly diverticuli fossae preputialis. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way as in females, both the sacs producing castoreum, of similar dimensions and size, and the circumanal glands, are situated in this region. The first of these in females open into the region of the clithoris and are the lateral diverticuli of this region (Gienc & Doboszyńska, 1972), whereas in males they open near the penis and are quite clearly diverticuli fossae preputialis. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Problems connected with the cyclic nature of spermatogenesis in the beaver have been examined by Ivanova (1961). A more detailed description has been given of the macro-and microscopic structure of the postpelvic region (Nikulin, 1954), where the so-called "preputial glands" producing castoreum, described by Kacnielson & Orlova (1954, 1956, have been distinguished, also termed by Gienc & Doboszyńska (1972) and Doboszyń-ska (1976Doboszyń-ska ( , 1978 in females as diverticula laterales fossae preputialis, and the glandulae circumanales producing the fatty secretion used by the animals to lubricate their fur (Doboszyńska, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the anatomical structure of the genital system in female beavers have shown that the true vagina of an adult animal (about 15 cm long and about 2 cm in diameter), ending in a short segment of the urogenital sinus, passes, together with the anus, by means of paired lateral recesses of the preputial fossa and paraproctial glands, into the pseudocloaea (Gienc & Doboszyńska, 1972;Doboszyńska, 1974). It was simultaneously found that the wall of the pseudocluaca, the lateral recesses of the preputial fossa, the clitoris, preputial folds of the clitoris and the uregenital sinus, are covered with flat stratified epithelium, cotrnifying and exfoliating irrespective of the phases of the sexual cycle (Doboszyńska, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the anatomical structure of the genital system in female beavers have shown that the true vagina of an adult animal (about 15 cm long and about 2 cm in diameter), ending in a short segment of the urogenital sinus, passes, together with the anus, by means of paired lateral recesses of the preputial fossa and paraproctial glands, into the pseudocloaea (Gienc & Doboszyńska, 1972; Doboszyńska, 0299] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation